2020
DOI: 10.5194/acp-20-4575-2020
|View full text |Cite
|
Sign up to set email alerts
|

Haze pollution under a high atmospheric oxidization capacity in summer in Beijing: insights into formation mechanism of atmospheric physicochemical processes

Abstract: Abstract. Under a high atmospheric oxidization capacity, the synergistic effect of the physicochemical processes in the atmospheric boundary layer (ABL) caused summer haze pollution in Beijing. The southern and southwestern areas, generally 60–300 km away from Beijing, were seriously polluted in contrast to Beijing, which remained clean. Southerly winds moving faster than 20–30 km h−1 since the early morning primarily caused haze pollution initiation. The PM2.5 (particulate matter with a dynamic equivalent dia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…They attributed this to stronger winter AHEs from elevated energy consumption for building heating systems (Lu et al, 2016), which readily accumulate in Beijing's frequently stable and shallow winter nocturnal boundary layer (Zhang et al, 2016), and more efficient nocturnal cooling in rural areas under frequent strong winter temperature inversions (Yang et al, 2013). Summertime nocturnal UHIIs are influenced more by the delayed release of heat stored within the urban fabric throughout the day (Oke et al, 1999;Wang et al, 2013), with a smaller proportion attributed to AHEs from residential air conditioning units (Zhao et al, 2018).…”
Section: Case Surface Parameters Ahesmentioning
confidence: 99%
See 2 more Smart Citations
“…They attributed this to stronger winter AHEs from elevated energy consumption for building heating systems (Lu et al, 2016), which readily accumulate in Beijing's frequently stable and shallow winter nocturnal boundary layer (Zhang et al, 2016), and more efficient nocturnal cooling in rural areas under frequent strong winter temperature inversions (Yang et al, 2013). Summertime nocturnal UHIIs are influenced more by the delayed release of heat stored within the urban fabric throughout the day (Oke et al, 1999;Wang et al, 2013), with a smaller proportion attributed to AHEs from residential air conditioning units (Zhao et al, 2018).…”
Section: Case Surface Parameters Ahesmentioning
confidence: 99%
“…The UHI effect is well known to exacerbate and prolong extreme temperature events (Li et al, 2015;Jiang et al, 2019). As heatwaves are becoming more frequent in our warming climate (Krayenhoff et al, 2018;Zhao et al, 2018), the number of people in China left vulnerable to heat-related illnesses is increasing (Tan et al, 2010;Bai et al, 2014;Gu et al, 2016). Most at risk from illnesses such as heat stroke are the elderly (Gu et al, 2016), of particular concern in China owing to its ageing population (Li et al, 2016), and those without air conditioning (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), the variation of PM2.5 concentration was more sensitive and responded rapidly to the wind shift from northerly to southerly, causing the PM2.5 concentration in Beijing to increase quickly from ~30 μg•m -3 to ~150 μg•m -3 , while southwest of Beijing (e.g., BD, SJZ, XT, and HD) the PM2.5 concentration increased rapidly to ~200 μg•m -3 . Research has revealed that the pollutant transport south of Beijing, especially in the southwest areas (the Taihang Mountains), is the most important contribution source of Beijing pollutants (Zhao et al, 2020). During the AP (approximately December 3; episode 3 in Fig.…”
Section: The Four Phases From Aerosol Pollution Development To Dissipmentioning
confidence: 99%
“…As a developing country with the largest population in the world, China's air quality has exhibited an obvious improvement trend in recent years (Sun et al, 2015;Cao et al, 2017). Regional air pollution in China is still serious, however, especially the heavy aerosol pollution (HAP) caused by fine particulate matter (PM 2.5 ) in winter, which has attracted attention worldwide (Zheng et al, 2015(Zheng et al, , 2019Cheng et al, 2016). Therefore, providing a reliable distribution of the PM 2.5 concentration of HAP, especially at any time and at any height in a given region, is particularly important in the quest for avoiding public health problems and providing government policymakers with help in designing effective controls (Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%